Exploring modes: connecting finger patterns to musical character in the orchestra classroom - Smit, Amie (Kansas State University, 2023)
To improve intonation and solidify finger placement when utilizing various finger patterns, I developed a series of lessons surrounding the study of the seven Greek modes of music. Each of the lessons introducing a new mode included singing solfege, analyzing and organizing the tetrachords into finger patterns (for violin, viola, cello), listening to an example of the mode, students’ reflective responses regarding the character of the mode, and students playing the scale of the mode on their instruments. Lessons that reinforced previously introduced modes incorporated opportunities to interact with the modes in a creative or responsive way. On two occasions, students created a short melody in one of the modes they had studied, performed it for the class, and let the class hear/decipher which mode was used. These creative performances served as an excellent assessment tool as students performed and responded to peer performances. Lessons were tailored for each age group and specific class proficiency. Through personal study, interaction with professors, and discussion with peers, my teaching has broadened and expanded in numerous directions while completing this degree. From reminders of good score study habits, rehearsal techniques, or healthy playing techniques to deep conversations surrounding equitable concert programming and social-emotional learning, I have been challenged to think about student learning and student growth in ways that will forever impact my teaching. Some changes might present themselves in small, seemingly insignificant ways, for example, holding the baton at a slightly different angle. Other changes such as having students sing and audiate pitches, introducing minor modes earlier than the method book, and connecting modes to musical character, composition, and improvisation were all inspired by researching effective sight-reading strategies and are much more noticeable to students and administrators. Additionally, some aspects of my teaching practices have been heightened, for example, spending more rehearsal time on playing technique and tone-building, teaching students more about each composer represented in the literature, and engaging students in creative coursework and lessons.
Keywords: Greek modes; Orchestra classroom; Intonation; Finger patterns